Research on Mechanical Properties of Silica Fume Cementitious Materials Excited by Wet Grinding Methods - Canhao Zhao; Ben Li; Kaihang Li; Zhuocheng Li (Buildings)
Silica fume (SF) has been widely used in engineering; however, its densification during transportation reduces its original pozzolanic activity. This paper investigates the effects of wet grinding and chemical activation on the mechanical properties and hydration products of silica fume in cement-based materials, revealing the mechanism by which wet grinding improves these properties. The results indicate that wet grinding effectively reduces the particle size of silica fume. Under optimal excitation conditions (250 r/min, 20 min), the median particle size is reduced to 12.1 μm, 2.27 times smaller than before excitation. The 28-day compressive strength of the silica fume cement paste reaches 60.8 MPa, 23.7% higher than that of the reference group. This approach effectively mitigates nano-agglomeration, enhances the pozzolanic activity of silica fume, and promotes AFt and C-S-H gel formation. The findings demonstrate that wet grinding activation can further enhance the utilization rate of silica fume.